The Battle of Gettysburg - Crewe, Sabrina and Dale Anderson (Milwaukee, WI Gareth Stevens Publishing, 2003)
Provides the following information: The Civil War Begins; The Armies Approach; The Battle; After the Battle; Time Line.
Keywords: Gettysburg, Battle of, Gettysburg, Pa., 1863.; United States - History - Civil War, 1861-1865 - Campaigns